C1q/TNF-related Protein 9 Inhibits High Glucose–Induced Oxidative Stress and Apoptosis in Retinal Pigment Epithelial Cells Through the Activation of AMPK/Nrf2 Signaling Pathway. (8th October 2020) - Cheng, Yuhong; Qi, Yun; Liu, Siwei; Di, Rong; Shi, Qiang; Li, Jiayu; Pei, Cheng
Diabetic retinopathy (DR) is one of the common complications of diabetes mellitus. C1q/TNF-related protein 9 (CTRP9) has been demonstrated to be associated with the progression of diabetes and relative complications. However, its role in DR and underlying action of mechanism are not yet well understood. In the present study, human retinal pigment epithelial ARPE-19 cells were cultured under high concentration of glucose to simulate hyperglycemia condition in vitro . Our results showed that the expression of CTRP9 was significantly decreased in high glucose (HG)–stimulated ARPE-19 cells. CTRP9 overexpression improved HG-caused reduction in cell viability of ARPE-19 cells. CTRP9 overexpression significantly attenuated HG-induced oxidative stress, as proved by decreased levels of reactive oxygen species and malondialdehyde, and increased superoxide dismutase activity. Moreover, CTRP9 also prevented apoptosis in ARPE-19 cells in response to HG stimulation with decreased caspse-3 activity and bax expression, as well as increased bcl-2 expression. In contrast, knockdown of CTRP9 aggravated HG-induced oxidative stress and apoptosis. Furthermore, CTRP9 significantly induced the activation of AMPK/Nrf2 pathway in HG-induced ARPE-19 cells. Notably, inhibiting AMPK or Nrf2 blocked the protective effect of CTRP9 on ARPE-19 cells exposed to HG stimulation. Taken together, our findings suggested a protective effect of CTRP9 on HG-induced ARPE-19 cells and a putative mechanism involving the activation of AMPK/Nrf2 signaling pathway.